Modelling of light photons detection in scintillation camera - Md Ali, S. F.; Xianling, D.; Muhammad Noor, Ahmad Shukri; Rokhani, Fakhrul Zaman; Hashim, Suhairul; Saripan, M. Iqbal (IEEE, 2013)
Silicone photomultiplier (SiPM) technology have been introduced recently for photons detection. This type of detector offer various advantages compare to the conventional photomultiplier tubes (PMTs). SiPM are smaller in size and thus consumes less space. Several researches have been conducted using SiPM for image acquisition in the field of medical imaging. The aim of this research is to model the intrinsic resolution of a scintillation camera using SiPM detector. Experiments are conducted to determine the optimum distance between the light source and the SiPM detector to obtain an intrinsic resolution of 3.7 mm. The resolution is base on previous research using Toshiba GCA 7100A platform with Sodium Iodide (NaI)scintillator (40 x 40 x 0.9525 cm3). Results revealed that the SiPM needs to be placed at a distance of 14.36 mm from the light source to represent the scintillation camera intrinsic resolution. It is concluded that the SiPM detector can be used to model the current scintillation camera intrinsic resolution and have a huge potential to replace the current photomultiplier tube detector.